Pengembangan Potensi Desa Wahyuharjo, Kapanewon Lendah, Kabupaten Kulon Progo - Visnhu, Bartolomeus Galih (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
KKN is an activity carried out by students as a form of service to certain village communities with their respective problems. The type of KKN program that is carried out is KKN Society or KKN which is carried out online. The location of the KKN was carried out in Wahyuharjo Village, Kapanewon Lendah, Kulon Progo Regency, Yogyakarta Special Region.. Kapanewon Lendah is one of the Kapanewon in the Special Region of Yogyakarta which has an astronomical location at 7° 93'22” south latitude and between 110° 23'08” East Longitude. Wahyuharjo is one of the villages in Kapanewon Lendah, Kulon Progo Regency, Yogyakarta Special Region which is located between Bumirejo and Tirtorahayu villages which has a residential area of 26.46 ha and an area of 101.84 ha of agricultural land. Wahyuharjo Village has various village potentials, especially in the field of natural wealth which if developed and utilized optimally will provide more benefits and benefits for the community. Based on the data we got during the KKN program, we also found that the people of Wahyuharjo Village also have handicrafts in the form of woven banana stems. So it can be concluded that the people of Wahyuharjo Village already have knowledge in terms of utilizing natural resources, so we want to provide wider knowledge and insight which aims to make the community more optimal in utilizing and developing the potential of natural resources owned by Wahyuharjo Village.